A Note on the Damping of Pure Replacement Cycles - Howrey, E. Philip (The Review of Economics and Statistics, 1965)
The purpose of a foreign exchange guarantee is not to discourage countries which should devalue from devaluing but to allow monetary authorities to cooperate freely and fully in reducing international monetary instability and to prevent devaluations from taking place which would not take place if adequate cooperative arrangements were available. In this context, it is revealing that the overwhelming majority of agreements concerning international monetary cooperation in the postwar world have contained exchange guarantees.15 Until some radical reforms, are introduced into the international monetary system, the stability of the system will, in large measure, depend on cooperation between the monetary authorities of the leading financial countries. One of the obstacles that has been encountered in this cooperation is the unwillingness of the various monetary authorities to accumulate large amounts of foreign exchange without some sort of exchange guarantee. I do not say the absence of an exchange guarantee is the only obstacle, but it has been, and is, one of the serious obstacles. An exchange guarantee is not a panacea for the world's monetary ills, however, it can make a valuable contribution toward international monetary stability.16